2021
DOI: 10.3389/fphys.2021.659777
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Oxidative Stress, Apoptosis, and Inflammation in Broiler Chickens With Wooden Breast Myopathy

Abstract: Wooden breast (WB) syndrome has emerged as a global myopathy in modern commercial broiler chickens, mainly affecting the pectoralis major muscle. Recent evidence suggests that WB myopathy is a systemic disease, which might be accompanied by other physiological disparities and metabolic changes. This study was conducted to systemically investigate the potential physiological changes in liver tissues as well as the possible mechanisms involved to enhance the understanding of the etiology. A total of 93 market-ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…In addition, relative heart weight also increased by breast conditions, so it is possible that the WB birds need larger heart to maintain the function. The liver is a primary metabolic organ for poultry that has numerous functions such as digestion, metabolism, biosynthesis, waste product removal, and detoxification ( Zaefarian et al, 2019 ; Xing et al, 2021 ). Birds with WB score 3 had greater absolute but not relative liver weights in comparison to those with normal breasts ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, relative heart weight also increased by breast conditions, so it is possible that the WB birds need larger heart to maintain the function. The liver is a primary metabolic organ for poultry that has numerous functions such as digestion, metabolism, biosynthesis, waste product removal, and detoxification ( Zaefarian et al, 2019 ; Xing et al, 2021 ). Birds with WB score 3 had greater absolute but not relative liver weights in comparison to those with normal breasts ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is was generally accepted that oxidative stress and inflammation are interconnected pathophysiological processes associated with many kinds of inflammatory diseases [ 54 ] and that the overproduction of inflammatory mediators could be used to determine oxidative stress. There is a connection between the suppression of the NF-κB signaling pathway and the activation of the Nrf2 signaling pathway, while Nrf2 overexpression suppresses NF-κB-DNA binding activity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found that PLA2 was upregulated due to the activation of mitogen-activate protein kinase cascades, which is linked to a wide range of extracellular stimuli such hormones, calcium mobilizing agents, oxidative stress, or osmotic challenges ( Lambert et al, 2006 ; Rubio et al, 2015 ). Furthermore, Greene et al (2020) and Xing et al (2021) both noted an upregulation of PLA2 in WB compared to the N samples, and they have linked this observation with increased production of reactive oxygen species in WB broilers. Additionally, multiple PLA2 suppressor proteins such annexin A1, A2, A4, and A5 were significantly upregulated in the WB samples ( p < 0.01).…”
Section: Resultsmentioning
confidence: 92%
“… Chao et al (2020) ’s product ion analysis result showed that the major fatty acid for the altered PE species 36:2 is linoleic acid, which is an omega 6 fatty acid and is characterized by its pro-inflammatory response. Increased inflammation has been observed in WB birds ( Young and Rasmussen, 2020 ; Xing et al, 2021 ), and it is possible the excess omega 6 fatty acids in WB SR membrane indicated the WB broilers could be suffering from distress.…”
Section: Resultsmentioning
confidence: 99%